A Benefit of New Costing Methods for the Strategic Management - Bohuslava Knapová (European Financial and Accounting Journal, 2009)
Strategic managerial decisions have the great influence on the growing performance of the company as an accounting entity and the successfulness in its business today. Managerial decisions on the strategic level of the management are concerned with the existing internal organizational and economic, responsibility structure of the accounting entity, which must create own strategy system in order to prosper under conditions of the external competitive environment. The strategic management is the conceptual and long-term starting point of the complete management. New costing methods, i. e. using of the target costing and life cycle costing, belong to the areas of the output oriented management and are applied in the strategic (long-term) management of product costs.
Keywords: M41; 650; Strategic management; Output oriented management; Managerial decisions; Strategy system; Target Costing; Life Cycle Costing